Portraits for Timpani: 50 Studies for Timpani - CIRONE, Anthony J. (Belwin Mills Publishing, 1976)
The 50 studies presented here are designed to increase the virtuosity and solo techniques for timpani playing. These pieces are composed with phrasing as the prime concern. The more ability a student has, the more music he will be able to produce from these etudes. In the same respect, a student's abilities will be developed as he performs these pieces in a musical manner.